Racial and Ethnic Disparities in Emergency Department Care and Health Outcomes Among Children in the United States - Zhang, Xingyu; Carabello, Maria; Hill, Tyler; He, Kevin; Friese, Christopher R.; Mahajan, Prashant (Frontiers in Pediatrics, 2019)
Background: There is an incomplete understanding of disparities in emergency care for children across various racial and ethnic groups in the United States. In this project, we sought to investigate patterns of emergency care utilization, disposition, and resource use in children by race and ethnicity after adjusting for demographic, socioeconomic, and clinical factors. Methods: In this cross-sectional study of emergency department (ED) data from the nationally representative National Hospital Ambulatory Medical Survey (NHAMCS), we examined multiple dimensions of ED care and treatment from 2005 to 2016 among children in the United States. The main outcomes include ED disposition (hospital admission, ICU admission, and in hospital death), resources utilization (medical imaging use, blood tests, and procedure use) and patient ED waiting times and total length of ED stay. The main exposure variable is race/ethnicity categorized as non-Hispanic white (White), non-Hispanic black (Black), Hispanic, Asian, and Other. Analyses were stratified by race and ethnicity and adjusted for demographic, socioeconomic, and clinical factors. Results: There were 78,471 pediatric (< 18 years old) ED encounters, providing a weighted sample of 333,169,620 ED visits eligible for analysis. Black and Hispanic pediatric patients were 8% less likely (aOR 0.92, 95% CI 0.91–0.92), and 16% less likely (aOR 0.86, CI 0.86–0.86) than Whites to have their care need classified as immediate/emergent. Blacks and Hispanics were also 28% and 3% less likely, respectively, than Whites to be admitted to the hospital following an ED visit (aOR 0.72, CI 0.72–0.72; aOR 0.97, CI 0.97–0.97). Blacks and Hispanics also experienced significantly longer wait times and overall visits as compared to Whites. Conclusions: Black and Hispanic children faced disparities in emergency care across multiple dimensions of emergency care when compared to non-Hispanic White children, while Asian children did not demonstrate such patterns. Further research is needed to understand the underlying root causes and long-term health consequences of these divergent patterns of racial disparities in ED care within an increasingly racially diverse cohort of younger Americans.